2016
DOI: 10.1055/s-0036-1588026
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Modified Albumin May Be a Novel Marker for Predicting Neonatal Neurologic Injury in Small-For-Gestational-Age Infants in Addition to Neuron-Specific Enolase

Abstract: This study aims to evaluate hypoxia/ischemia and oxidant stress, and negative neurodevelopmental outcomes in small-for-gestational-age (SGA) infants. Two study groups were established as SGA and appropriate-for-gestational-age (AGA) infants. SGA infants were allocated asymmetric and symmetric SGA infants. Serum levels of neuron-specific enolase (NSE), ischemia-modified albumin (IMA), malondialdehyde (MDA), total antioxidant capacity (TAC), and total oxidant status (TOS) were determined and oxidative stress ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the study of Tayman et al, 21 the mean IMA value of appropriate for gestational age (AGA) babies was higher in the study group than that of the control group. In our study, the absorbance method was used as the measurement method, and the preoperative mean IMA values of babies with congenital heart disease in our study were still lower than AGA babies of the mentioned study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the study of Tayman et al, 21 the mean IMA value of appropriate for gestational age (AGA) babies was higher in the study group than that of the control group. In our study, the absorbance method was used as the measurement method, and the preoperative mean IMA values of babies with congenital heart disease in our study were still lower than AGA babies of the mentioned study.…”
Section: Discussionmentioning
confidence: 92%
“…There are literature studies commenting on the relationship of IMA with hypoxia and ischemia, transient neonatal tachypnea, intrauterine growth retardation, respiratory distress syndrome, and low birth weight babies. [8][9][10][19][20][21] However, there is no study investigating the relationship between congenital heart defects and IMA.…”
Section: Discussionmentioning
confidence: 99%
“…These would have also been excluded for other reasons such as not meeting FGR definition (very low birth weight, preterm birth only), not assessing neurodevelopmental outcomes, or that no blood biomarkers were assessed. One study was excluded as it did not include neurodevelopmental assessments (36) and another was excluded as it reported only the presence of brain injury for the FGR cohort (37). Finally, one study was a twin study but was excluded as it did not separate the FGR twins from the normally grown pair for comparison (38).…”
Section: Resultsmentioning
confidence: 99%
“…Small for gestational age (SGA) differs from FGR in that it is solely defined by birthweight <10th percentile (3)(4)(5). We observed, however, that the studies included for full text review that included SGA cohorts either did not have a cohort of NG infants as controls or did not conduct a neurodevelopmental assessment >12 months of age for the NG cohort (31)(32)(33)(34)(35)(36)(37). Therefore, even when broadening the inclusion criteria to include SGA infants, our search of the current literature still only yielded one study that met all inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…While Mazarico et al [52] observed significantly higher levels of NSE in fetal umbilical arterial and maternal blood at birth in FGR, other studies have not observed this alteration [54, 58]. Tayman et al [59] observed increased NSE levels in peripheral venous blood 12 h after birth for SGA compared to AGA neonates; however, levels were decreased in asymmetric SGA compared to symmetric SGA neonates.…”
Section: Potential Biomarkers Of Interestmentioning
confidence: 99%